How Proficient is Proficient Enough?: A Look at Proficiency in ESL for Academic Success - Berardo, Marcellino (Issues in Language Instruction, 2017)
We teach English to international students for the purpose of academic achievement at the University of Kansas. The assumption is that students cannot be successful in university classes without the ability to use academic English well. This is most obvious at the lower levels. If the student cannot understand any spoken or written English, then s/he cannot take notes, read textbook chapters, write papers, take exams, or participate in class discussion. This assumption also implies that as the student’s English improves, proficiency will become less of a factor in academic success. This essay is intended to help us discuss assumptions associated with language proficiency and academic success and to identify how well students need to be able to use English in order to fulfill the university’s ESL requirement and be successful in their chosen academic program, at least as far as language is concerned. To this end, I begin by characterizing different kinds of proficiency. Then I highlight the literature reviews in this issue, one by Jennifer Hornbaker and one by Parul Sood, that bring up issues related to using proficiency tests as the sole indicators of linguistic readiness for academic success at the university.